2022
DOI: 10.1038/s41598-022-07298-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability in essential oil composition and biological activity of Rosmarinus officinalis L. accessions in the western Himalaya

Abstract: Rosmarinus officinalis L. is an imperative herb used in pharmaceutical yet knowledge on chemical and activity profile of essential oil (EO) to harvest seasons and accessions from the Himalayan region is limited. Thus, accessions were evaluated to determine the EO content, compositional, antimicrobial, and cytotoxic potential of rosemary in different harvest seasons during 2018‒2019. EO content was 30.5% higher in IHBT/RMAc-1 compared with IHBT/RMAc-2 accession while 27.9% and 41.6% higher in the autumn as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 59 publications
3
17
0
1
Order By: Relevance
“…When camphor content was compared by the growth stages, higher amounts were found in the pre-flowering stage. Differences in the camphor content were also reported in rosemary by other researchers, such as 11.25%-20.41% (Gürbüz et al, 2017), 1.10%-18.80% (Flamini et al, 2021), 12.40% (Christopoulou et al, 2021, 17.30%-19.07% (Dzięcioł, 2021), 14.39%-17.17% (Micić et al, 2021), 10.01%-16.20% (Elyemni et al, 2022), 7.05%-31.50% (Rathore et al, 2022), 29.46%-31.92% (Yeddes et al, 2022), 18.26% (Karakaş and Bekler, 2022). Similar to what we detected in our study, Afshar et al (2021) reported that camphor content decreased from spring (8.19%) to summer (6.95%).…”
Section: Chemical Composition Of Essential Oilsupporting
confidence: 54%
See 1 more Smart Citation
“…When camphor content was compared by the growth stages, higher amounts were found in the pre-flowering stage. Differences in the camphor content were also reported in rosemary by other researchers, such as 11.25%-20.41% (Gürbüz et al, 2017), 1.10%-18.80% (Flamini et al, 2021), 12.40% (Christopoulou et al, 2021, 17.30%-19.07% (Dzięcioł, 2021), 14.39%-17.17% (Micić et al, 2021), 10.01%-16.20% (Elyemni et al, 2022), 7.05%-31.50% (Rathore et al, 2022), 29.46%-31.92% (Yeddes et al, 2022), 18.26% (Karakaş and Bekler, 2022). Similar to what we detected in our study, Afshar et al (2021) reported that camphor content decreased from spring (8.19%) to summer (6.95%).…”
Section: Chemical Composition Of Essential Oilsupporting
confidence: 54%
“…Similar to the camphor content, the highest values for the 1.8-cineole content were obtained in the pre-flowering stage (22.61%). When compared the 1.8-cineole content with the earlier studies, diverse results were found, such as 6.19%-10.52% (Gürbüz et al, 2017), 41.25%-45.96% (Yıldırım, 2018), 37.50% (Khanjani et al, 2021), 10.81% (Xylia et al, 2021), 17.79%-23.40% (Micić et al, 2021), 26.40%-49.10% (Flamini et al, 2021), 40.10% (Christopoulou et al, 2021, 30.89%-31.61% (Dzięcioł, 2021), 28.97%-32.18% (Elyemni et al, 2022), 32.50%-51.79% (Rathore et al, 2022), 30.26% (Mwithiga et al, 2022), 25.26%-29.15% (Yeddes et al, 2022), 11.86% (Karakaş and Bekler, 2022).…”
Section: Chemical Composition Of Essential Oilmentioning
confidence: 99%
“…Previous studies showed that the antibacterial activities of EOs from different plant species were mainly associated with their chemical compositions, especially oxygenated monoterpenes, which usually occur in high amounts [ 73 , 74 , 75 ]. In the present study, the results obtained for antibacterial activity correspond with the great antioxidant activity of BCEO.…”
Section: Discussionmentioning
confidence: 99%
“…N (carrier gas) was used at a 1.05 mL min −1 flow rate; the temperature of the oven was maintained at 70 • C for 3 min and subsequently risen to 220 • C for 5 min at a rate of 4 • C min −1 . The maintained temperature of the injector was 220 • C while that of the detector was 250 • C. The settings of temperature lineup, injection volume, and carrier gas utilized to execute GC and GC/MS were similar to the detailed procedure for Rosmarinus officinalis L. in Rathore et al (2022). To identify components from areas of GC peaks, a series of hydrocarbons was used for retention index (RI) determination without the use of any correction factor.…”
Section: Identification and Determination Of Essential Oil Componentsmentioning
confidence: 99%